1999
DOI: 10.4269/ajtmh.1999.61.280
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage expression of class II major histocompatibility complex gene products in Paracoccidioides brasiliensis-infected mice.

Abstract: Abstract. C57Bl/6 isogenic mice infected with Paracoccidioides brasiliensis strains showed a disruption in the expression of Ia antigen. Expression slowly decreased during the course of the infection with a slight variation dependent on the route of inoculation and the fungal strain used, but production of interferon-␥ and tumor necrosis factor-␣ were observed. Suppression of Ia antigen expression and depression of the immunoproliferative responses of spleen cells were strongly correlated with nitric oxide lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
7

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
0
13
1
7
Order By: Relevance
“…‫,ء‬ significant difference (p Ͻ 0.05) between AG-treated vs untreated group. MHC class II expression (8) and that macrophages from susceptible mice are less effective in Ag presentation (25). However, our results with IA k expression are in contrast to those reports, as we showed that macrophage IA k expression of susceptible mice was not impaired and actually was higher in susceptible than in resistant mice throughout the infection.…”
Section: Figurecontrasting
confidence: 57%
See 4 more Smart Citations
“…‫,ء‬ significant difference (p Ͻ 0.05) between AG-treated vs untreated group. MHC class II expression (8) and that macrophages from susceptible mice are less effective in Ag presentation (25). However, our results with IA k expression are in contrast to those reports, as we showed that macrophage IA k expression of susceptible mice was not impaired and actually was higher in susceptible than in resistant mice throughout the infection.…”
Section: Figurecontrasting
confidence: 57%
“…Macrophage responses were assessed by the production of NO, TNF, and H 2 O 2 and by the expression of IA k molecules. These molecules were selected for analysis based on previous reports suggesting that they might influence the outcome of P. brasiliensis infection (7,8,23,24). Minor differences in macrophage responses of susceptible or resistant mice were observed when IA k expression and H 2 O 2 production were analyzed, while major differences were related to NO and TNF production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations